2006
DOI: 10.1111/j.1540-8175.2006.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

The Double Jeopardy of Blunt Chest Trauma: A Case Report and Review

Abstract: Cardiac injury, specifically valvular rupture, must be considered after blunt chest trauma even in previously healthy patients. Isolated mitral regurgitation (MR) and tricuspid regurgitation (TR) due to blunt chest trauma are rare phenomena. More unique is simultaneous complete papillary muscle rupture of the mitral valve (MV) and tricuspid valve (TV) with only four patients being previously reported in the literature. This case describes a patient with complete transection of the posteromedial papillary muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…5 The tricuspid valve may be involved alone 6 or with mitral valve injury and regurgitation. 7 Other associated injuries may include atrial septal rupture with complete heart block, rupture of right ventricular papillary muscle and bifascicular block, interventricular septal rupture, avulsion or dissection of the right coronary artery, and left anterior descending artery thrombosis causing myocardial infarction. Correct diagnosis is missed acutely because of coexisting multisystem involvement and the subtleness of abnormal physical signs.…”
Section: Discussionmentioning
confidence: 99%
“…5 The tricuspid valve may be involved alone 6 or with mitral valve injury and regurgitation. 7 Other associated injuries may include atrial septal rupture with complete heart block, rupture of right ventricular papillary muscle and bifascicular block, interventricular septal rupture, avulsion or dissection of the right coronary artery, and left anterior descending artery thrombosis causing myocardial infarction. Correct diagnosis is missed acutely because of coexisting multisystem involvement and the subtleness of abnormal physical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the incidence of tricuspid valve involvement as a result of blunt chest trauma has been tradition ally considered low when compared with other cardiac valves, on review of the literature, we found that an increasing number of cases involving the tricuspid valve apparatus are now being reported 6 9 . Although most of these cases were associated with motor vehicle collisions, some have been reported after patients had falls from a height.…”
mentioning
confidence: 84%
“…Although most of these cases were associated with motor vehicle collisions, some have been reported after patients had falls from a height. An approximately equal proportion of papillary muscle and chordae tendinae rupture cases have been reported 6 9 . It is important that we highlight the fact that our search was limited to cases listed in the English literature and only involving adult patients.…”
mentioning
confidence: 99%
“…Jahrhundert mehren sich seit den 70er Jahren die Fallbeschreibungen zur traumatischen Mitralklappendysfunktion [19,28,59,73,83]. In den meisten Fällen sind Verkehrsunfälle mit Auto [2,17,18,22,23,29,36,37,51,54,62,66,67,69,70,78,79,84,[88][89][90]93] oder Motorrad [10,25,35,41,50,76] Ursachen der Klappenverletzungen. Nicht selten werden Stürze aus großer Höhe [6,46,52,80,94,96] und Schlageinwirkungen vor die Brust [12,15,32,33,63,75,87] als ursäch-lich beschrieben.…”
Section: Unfallursacheunclassified